(untitled) (International journal of artificial intelligence, 2024)
This article studies the effectiveness of using information technologies and marketing tools in the privatization of state assets. During the study, the speed and transparency of privatization through electronic trading platforms were analyzed, and the possibilities of increasing demand for state property through marketing strategies were studied. According to empirical data, the use of information technologies in these processes helps to increase budget revenues and accelerate the trading process. The results showed that it is an important factor in developing cooperation between the state and the private sector.